ChatGPT and Personalised Learning: Reshaping Pedagogical Approaches in the VUCA Age - FX. Risang Baskara (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This paper explores the impact of OpenAI's ChatGPT on personalized learning in higher education during the VUCA (Volatility, Uncertainty, Complexity, Ambiguity) era. It investigates how ChatGPT can improve individualized learning to tackle VUCA challenges in higher education. Although previous studies have noted AI's potential in education, there's limited in-depth research on ChatGPT's role in personalized learning. This study stands out by providing new insights into the intersection of AI and higher education pedagogy through a theoretical analysis based on primary and secondary data sources, including academic literature and case studies. Key findings show that ChatGPT's advanced language capabilities can create personalized learning environments, addressing VUCA challenges. It suggests that AI tools like ChatGPT are crucial for pedagogical innovation and student engagement, marking a significant shift in education where traditional methods meet technological advancements. These findings have important implications for educators, policymakers, and AI developers, highlighting the need to integrate AI tools like ChatGPT in higher education curricula to improve teaching and learning experiences, and prepare students for a dynamic world. The paper concludes by urging further academic research to explore the broader implications of AI in education and address the challenges of this transformative process.Makalah ini mengeksplorasi dampak ChatGPT dari OpenAI terhadap pembelajaran personalisasi dalam pendidikan tinggi di era VUCA (Volatility, Uncertainty, Complexity, Ambiguity). Makalah ini menyelidiki bagaimana ChatGPT dapat meningkatkan pembelajaran individual untuk mengatasi tantangan VUCA dalam pendidikan tinggi. Meskipun studi sebelumnya telah mencatat potensi AI dalam pendidikan, penelitian mendalam mengenai peran ChatGPT dalam pembelajaran personalisasi masih terbatas. Studi ini menonjol dengan memberikan wawasan baru tentang persinggungan AI dan pedagogi pendidikan tinggi melalui analisis teoritis berdasarkan sumber data primer dan sekunder, termasuk literatur akademik dan studi kasus. Temuan utama menunjukkan bahwa kemampuan bahasa canggih ChatGPT dapat menciptakan lingkungan pembelajaran yang personalisasi, menangani tantangan VUCA. Makalah ini menyarankan bahwa alat AI seperti ChatGPT sangat penting untuk inovasi pedagogi dan keterlibatan siswa, menandai pergeseran penting dalam pendidikan di mana metode tradisional bertemu dengan kemajuan teknologi. Temuan ini memiliki implikasi penting bagi pendidik, pembuat kebijakan, dan pengembang AI, menyoroti perlunya mengintegrasikan alat AI seperti ChatGPT dalam kurikulum pendidikan tinggi untuk meningkatkan pengalaman mengajar dan belajar, serta mempersiapkan siswa untuk dunia yang dinamis. Makalah ini menyimpulkan dengan mendesak penelitian akademik lebih lanjut untuk mengeksplorasi implikasi yang lebih luas dari integrasi AI dalam pendidikan dan mengatasi tantangan proses transformasi ini.